ADAPTIVE LEADERSHIP IN DIGITAL ERA: CASE STUDY OF RIDWAN KAMIL - Hoerudin, Cecep (CosmoGov: Jurnal Ilmu Pemerintahan, 2020)
The era of technological disruption requires organizational leaders to find methods to develop their leadership capacity. This study aims to analyze the effectiveness of adaptive leadership in the digital age by taking a case study of Ridwan Kamil's leadership in West Java. The research method used in this research is a descriptive qualitative method. This research data collection technique uses literature studies by tracing sources originating from government documents, media, books, and scientific journals that are relevant to this study. The analysis of Ridwan Kamil's leadership was carried out using organizational communication theory. The results found that the adaptive leadership pattern gave Ridwan Kamil an opportunity to make many policy innovations during his leadership in West Java. Its dynamic nature makes it able to utilize its position to make changes in the form of innovation programs based on technology. The structure and agent dilemmas in his leadership can be overcome through the 4 approaches contained in the adaptive leadership.gb777